Expression skill development in the arabic language to non-native speakers - Munawwar Mustafa Muhammad,; Zamri Arifin, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Learners Arabic from non-native speakers face many difficulties while learning this language. The research has proven the weakness of students in the skills of expression of both types oral and written. This is what the research has found through material expression of obvious weakness in the skills. Among them are the lack of ideas, the lack of coherence, the large number of linguistic and grammatical errors and misspellings, poor punctuation, as well as a lack of desire to express orally or in writing. Since learning the Arabic language is not easy, in addition to the teacher often suffer from difficulty in learning and teaching this skill, it has prompted us to write this topic. This research offers some solutions to overcome the problems, and the development ofthis skill to the students non-Arabic. Then to enrich how to handle essay, and to solve the problems of weak students in the expression and treatment, as well as linking the rest of the branches of language expression.